Household mortuary practices in a South Andean village (first millennium AD) - Salazar, Julián (2012)
This research presents new data about South Andean mortuary practices and the construction of kinship relations, generated in recent field researches carried out in Early Ceramic Period (ca. 500 BC to AD 850) contexts from Tafí Valley, Northwestern Argentina. Our research project aims to establish relationships between daily practices and social reproduction household strategies, and to analyze materiality active role in the construction of kinship relations and identity. Consequently we have carried out field work in residential compounds in La Bolsa 1 site.